Makna Ritual Bokas Bagi Umat Hindu Kaharingan Di Desa Kalahien Kecamatan Dusun Selatan Kabupaten Barito Selatan - Sulandra Sulandra (Tampung Penyang, 2022)
Ritual is a matter relating to ritual in its full sense, it is a series of process activities carried out by someone who has a symbolic purpose in a certain series of events. This ritual can be used as a tradition in certain groups. The ritual can be done once or twice a week or whenever. The meaning of Bokas is often also pronounced in full as 'bokas ego', which is a crowd ceremony or large-scale party, as an expression of joy, whether held individually, or in cooperation in family groups, or in collaboration with other residents.